Vzdělávání žen v zemích Evropské unie - Pražanová, Šárka (Univerzita Pardubice, 2006)
Tato bakalářská práce se zabývá tématem vzdělávání žen v zemích Evropské unie.V teoretické části jsem se zaměřila na vzdělávání dospělých, kde se zmiňuji o České republice a konkrétních zemí Evropské unie. Cílem praktické části je obeznámení se se současnou situací vzdělávání žen v České republice.

This bachelor work deals with the women´s education in the European union.In theoretic part I target the further education I made reference to Czech Republic and some concrete states of the European Union. The point of practical part is acquaint oneself with the situation of women education in Czech Republic in this time.
Women education in states of the European union
Keywords: educaiton; forms; Czech Republic; European Union; women; Vzdělávání; formy; Česká Republika; Evropská Unie; ženy